Waste Water - Treatment and Reutilization 2011
DOI: 10.5772/16154
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Ammonium Oxidation in Waste Water -An Isotope Hydrological Perspective

Abstract: Excess nitrogen components must be removed from wastewater to protect the quality of the water bodies that it will be eventually discharged to. A conventional wastewater treatment system for nitrogen removal is often involved with two processes, nitrification and denitrification. Nitrification is mostly achieved by complete oxidation of ammonium (NH 4 +) to nitrite (NO 2-) by the appropriate aerobic bacteria and then oxidation of the nitrite to nitrate ion (NO 3-) by another variety of aerobic bacteria. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Therefore, ammonia and nitrite removal should occur in a single reactor. In fact, Xiao et al (2009) confirmed the coexistence of nitrifiers, denitrifiers, and anammox bacteria in a single batch sequencing reactor by using PCR-DGGE, and justified that ammonia removal occurred due to the growth of aerobic bacteria in the surface and anaerobic bacteria inside the biofilm. According to the authors, aerobic bacteria supply nitrite to anammox bacteria.…”
Section: Performance Of Anaerobic and Anoxic Reactors For Removal Of Organic Matter And Nitrogenmentioning
confidence: 53%
See 2 more Smart Citations
“…Therefore, ammonia and nitrite removal should occur in a single reactor. In fact, Xiao et al (2009) confirmed the coexistence of nitrifiers, denitrifiers, and anammox bacteria in a single batch sequencing reactor by using PCR-DGGE, and justified that ammonia removal occurred due to the growth of aerobic bacteria in the surface and anaerobic bacteria inside the biofilm. According to the authors, aerobic bacteria supply nitrite to anammox bacteria.…”
Section: Performance Of Anaerobic and Anoxic Reactors For Removal Of Organic Matter And Nitrogenmentioning
confidence: 53%
“…These reactions are widely known and have been successfully applied in most wastewater treatment systems (Egli et al, 2001). However, this process has some limitations when the objective is to treat effluents containing high concentrations of nitrogen and low concentration of carbon (low C / N ratio) since there are difficulties in the transfer of large amounts of oxygen necessary for nitrification and the need for a large amount of biodegradable organic matter in the denitrification phase (Xing and Clark, 2012). Fish farming effluents are characterized by the high concentration of biochemical oxygen demand (BOD) and the presence of organic and inorganic matter; in this way the efficiency of the process can be impaired and other processes must be explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation